Radiobiologically optimized couch shift: A new localization paradigm using cone‐beam CT for prostate radiotherapy. Issue 10 (23rd September 2015) - Huang, Yimei; Gardner, Stephen J.; Wen, Ning; Zhao, Bo; Gordon, James; Brown, Stephen; Chetty, Indrin J.
Abstract : Purpose: To present a novel positioning strategy which optimizes radiation delivery by utilizing radiobiological response knowledge and evaluate its use during prostate external beam radiotherapy. Methods: Five patients with low or intermediate risk prostate cancer were evaluated retrospectively in this IRB‐approved study. For each patient, a VMAT plan with one 358° arc was generated on the planning CT (PCT) to deliver 78 Gy in 39 fractions. Five representative pretreatment cone beam CTs (CBCT) were selected for each patient. The CBCT images were registered to PCT by a human observer, which consisted of an initial automated registration with three degrees‐of‐freedom, followed by manual adjustment for agreement at the prostate/rectal wall interface. To determine the optimal treatment position for each CBCT, a search was performed centering on the observer‐matched position (OM‐position) utilizing a score function based on radiobiological and dosimetric indices (EUDprostate, D 99prostate, NTCPrectum, and NTCPbladder ) for the prostate, rectum, and bladder. We termed the optimal treatment position the radiobiologically optimized couch shift position (ROCS‐position). Results: The dosimetric indices, averaged over the five patients' treatment plans, were (mean ± SD) 79.5 ± 0.3 Gy (EUDprostate ), 78.2 ± 0.4 Gy ( D 99prostate ), 11.1% ± 2.7% (NTCPrectum ), and 46.9% ± 7.6% (NTCPbladder ). The corresponding values from CBCT at the OM‐positions were 79.5 ± 0.6 Gy (EUDprostate ), 77.8 ± 0.7 Gy ( D 99prostate ), 12.1% ± 5.6% (NTCPrectum ), and 51.6% ± 15.2% (NTCPbladder ), respectively. In comparison, from CBCT at the ROCS‐positions, the dosimetric indices were 79.5 ± 0.6 Gy (EUDprostate ), 77.3 ± 0.6 Gy ( D 99prostate ), 8.0% ± 3.3% (NTCPrectum ), and 46.9% ± 15.7% (NTCPbladder ). Excessive NTCPrectum was observed on Patient 5 (19.5% ± 6.6%) corresponding to localization at OM‐position, compared to the planned value of 11.7%. This was mitigated with radiobiologically optimized localization, resulting in a reduced NTCPrectum value of 11.3% ± 3.5%. Overall, the treatment position optimization resulted in similar target dose coverage with reduced risk to rectum. Conclusions: These encouraging results illustrate the potential advantage of applying radiobiologically optimized correction for online image‐guided radiotherapy of prostate patients.